Optimizing Financial Decision-Making: Use of Relevant Costing Techniques in Manufacturing Businesses in the Philippines - Bongalonta, Atty. Michael B. (Future Science / FSH-PH Publications, 2025)
This study investigates the application and effectiveness of relevant costing among manufacturing businesses in Bulan, Sorsogon, with an emphasis on their impact on business performance. The research specifically assesses the extent to which relevant costing principles—such as identification of relevant and irrelevant costs, incremental analysis, pricing and cost control decisions, investment evaluation, and decision-making under resource constraints—are utilized by local manufacturing owners. Additionally, it examines key business performance indicators including gross profit rate, operating profit rate, and production yield rate, and explores the relationship between relevant costing utilization and business performance outcomes. Employing a quantitative research design that integrates descriptive and correlational approaches, the study surveyed 94 manufacturing business owners from a population of 124 registered entities, with data drawn from official local government records and audited financial statements spanning 2022 to 2025. Descriptive statistics revealed that relevant costing is “sometimes” applied in decision-making processes, with pricing and cost control decisions showing relatively higher utilization compared to incremental analysis and investment evaluation. Business performance analysis indicated low profitability levels, reflected by a gross profit rate of 17.46% and an operating profit rate of 3.75%, while production efficiency, measured by production yield rate, was moderate at 83.57%. Canonical Correlation Analysis established a statistically significant moderate relationship between relevant costing practices particularly in pricing, cost control, and investment appraisal and financial performance indicators.However, the inconsistent application of these practices limits their potential to fully enhance profitability, suggesting that other factors such as market dynamics and operational capabilities also influence business outcomes.